Colour vision and food selection of Callosciurus finlaysonii (Sciuridae) in tropical seasonal forests. (29th July 2015) - Tamura, Noriko; Fujii, Yukiko; Boonkeow, Phadet; Kanchanasaka, Budsabong
Abstract: Finlayson's squirrel is frugivorous and distributed throughout the tropical seasonal forests of South-East Asia. To understand the resource use of tree squirrels in a tropical forest ecosystem, colour vision and fruit selection of Finlayson's squirrel were investigated. Under laboratory conditions, this species possesses dichromatic colour vision; it can discriminate white, yellow, violet, brown and black versus green similar to leaves, but it cannot discriminate orange and red versus green. In addition, squirrels can discriminate pale pink, pink and dark red versus green but cannot discriminate red versus green due to its similar lightness and chroma. Through field observations, squirrels selected black or brown fruits and fed on the mature seeds although fruits of various colours appear on a tree, such as green, orange, yellow, pink or white ones including immature seeds. Brown, violet or black fruits accounted for 87% of those fruits consumed by these squirrels, whereas those with yellow, orange or red colour accounted for only 7%. The dichromatic colour vision in Finlayson's squirrel may be useful for selecting ripe fruits in preference to unripe ones.